Pancasila dan pluralisme Indonesia: Strategi penguatan toleransi beragama dan integrasi sosial - Sulistyawati, Santi Maya (Maliki Interdisciplinary Journal, 2026)
This article discusses the important role of Pancasila as the foundation of pluralism in Indonesia and the importance of strategies to strengthen tolerance among religious communities and social integration. Indonesia is a nation with a diversity of ethnic groups, regional languages, and officially recognized religions. This diversity is an important asset but also a challenge in maintaining unity in religious tolerance. Pancasila contributes to the ideology of a country that emphasizes the importance of differences, so that pluralism is not only a recognition of the existence of other religions, but also an active connection to build harmony among religious communities. This article emphasizes that religious tolerance and social integration are key to preventing social conflict and radicalism that arise from a lack of appreciation for differences between religious communities. Religious tolerance, as discussed by the government, is an important guideline for balancing relations between majority and minority groups. In addition, multicultural psychology plays an active role in shaping individuals who are aware of diversity. In this era of globalization, Pancasila faces new challenges from external ideologies and technological developments. Critical reflection is needed to reorganize Pancasila so that it remains relevant in addressing issues such as social inequality and digital transformation.